[PbX6]4− modulation and organic spacer construction for stable perovskite solar cells. Issue 11 (27th September 2022) - Wang, Lian; Chang, Bohong; Li, Hui; Wu, Yutong; Liu, Zhen; Pan, Lu; Yin, Longwei
Abstract : This review summarizes the influence mechanism, research progress and future perspectives on perovskite stability from the perspectives of [PbX6 ] 4− octahedra and organic spacers. Abstract : The unique lattice structure and chemical bonding nature of perovskites endow them with illustrious photovoltaic properties, which have enabled perovskite solar cells (PSCs) to achieve a power conversion efficiency (PCE) of 25.7%, approaching that of commercial silicon-based devices. However, the instability originating from the soft ionic lattice characteristics of perovskites makes the device lifespan much shorter than the industry demand of 20 years. Herein, the influence of the lattice structure on the stability of perovskites is thoroughly profiled from the perspectives of [PbX6 ] 4− octahedra and organic spacers, which serve as a supporting skeleton and structural stabilizer, respectively. The crystal structure, corresponding photophysical properties and stability performance are first dissected, followed by a discussion on the essential roles of octahedra and organic spacers in the environmental degradation, ion migration, phase segregation behavior, lattice strain and phase transition. Furthermore, the typical strategies to enhance the intrinsic and extrinsic stability of perovskites are summarized with regard to octahedral modulation and organic spacer construction, including component engineering for octahedral reinforcement, management of lattice defects and stress, and dimensional design to stabilize the perovskite lattice. Based on this, several key scientific issues and promising future directions are presented to enhance the stability of PSCs and promote their commercialization.